EVALUATION OF CRITERIA FOR THE DIGITALIZATION OF AGRICULTURAL MACHINERY - Nedeljković, Miroslav; Budimir, Mate; Branković, Bojan (Economics of Agriculture, 2026)
In the paper, using the multi-criteria decision-makingmethod SiWeC, the digitization criteria were evaluated onthe example of medium- and heavy-duty tractors. A fuzzyvariant of the multi-criteria decision-making method wasused in order to obtain as precise assessment of the giventen qualitative criteria as possible. The results show that,according to the expert evaluation, the technical criterion“Precision of operations” gained the most importance,while immediately after them in importance were thecriteria related to the level of work automation and digitalconnectivity. The results show important implications fordecision makers, technology producers and the shaping ofagricultural policy. In the future, the model needs to beexpanded with impact criteria, and the number of decisionmakers who would give a practical contribution, as wellas a base for further development of the applied researchmethod, should be increased.